MOISTURE REMOVAL RATE FOR REGENERATION AND DEHUMIDIFICATION PROCESS BETWEEN DESICCANT-AIR CONTACT SYSTEMS ON PACKED LAYER USING SOLAR ENERGY - Yohana, Eflita (Departemen Teknik Mesin, Fakultas Teknik, Universitas Diponegoro, 2009)
MOISTURE REMOVAL RATE FOR REGENERATION AND DEHUMIDIFICATION PROCESS BETWEEN DESICCANT-AIR CONTACT SYSTEMS ON PACKED LAYER USING SOLAR ENERGY